Synthesis of Azabicyclic Building Blocks for Daphniphyllum Alkaloid Intermediates Featuring N‐Trichloroacetyl Enamide 5‐endo‐trig Radical Cyclizations. Issue 10 (24th September 2019) - Jansana, Sergi; Coussanes, Guilhem; Puig, Jordi; Diaba, Faiza; Bonjoch, Josep
Abstract: A general procedure is reported for the synthesis of cis ring fused azapolycyclic compounds bearing an all‐carbon quaternary stereocenter at the ring fusion and an adequate functionalization for the assembly of new rings leading to advanced synthetic intermediates for Daphniphyllum alkaloid synthesis. The key carbon−carbon bond‐forming step in this approach is a radical cyclization of an N ‐cycloalkenyl trichloroacetamide derivative involving a tetrasubstituted enamide to achieve polyfunctionalized lactams. Abstract :